Growth and production of cowpea cultivated with liming and nitrogen fertilization in the Eastern Amazon - Garcia Costa, Milton; de Oliveira Ferreira, Eric Victor; Moura Oliveira, Thiago Caio; Pereira Maciel, Gutierre; Sosa Duque, Francisco José; Cunha Pereira, Wanderson (Revista Ceres, 2025)
In the northeastern of Pará, cowpea is one of the main protein sources of the population. This study aimed to evaluate the effects of liming, the P and K mineral fertilization, and the combination of seed inoculation with Rhizobium associated with mineral N supplementation in the growth and production of cowpea cultivars. Two experiments were carried out in two consecutive years at the Federal Rural University of Amazonia (Capitão Poço-PA). A randomized block experimental design with subdivided plots was used with four replications, two cowpea cultivars (BRS Tapaihum and BRS Marataoã) and six fertilization and liming treatments: i) without fertilization and without liming; ii) P and K mineral fertilization, liming and seed inoculation with Rhizobium; iii) P and K mineral fertilization and seed inoculation with Rhizobium; iv) N, P and K mineral fertilization and liming; v) P and K mineral fertilization and liming; and vi) N, P and K mineral fertilization, liming and seed inoculation with Rhizobium. Cowpea responded to liming and P and K mineral fertilization, but not N fertilization. There was no difference between the supply of N through seed inoculation or mineral fertilization. Thus, it is suggested to inoculate seeds with Rhizobium in order to maintain the soil N reserve.